The Development of a Caregivers’ Participation Model on Infection Prevention Behaviors, Satisfaction towards Nursing Services, and Readmission Rates of Pediatric Cancer Patients Receiving Chemotherapy - Unahasuwan, Ubonwan; Noimuenwai, Premruetai; Prasertsri, Nusara (Journal of The Royal Thai Army Nurses, 2023)
The purposes of this research and development study were to 1) develop a caregivers’ participation model for caregivers of pediatric cancer patients receiving chemotherapy and 2) to study the results of the model. The sample consisted of 30 pediatric cancer patients and 30 caregivers recruited by purposive sampling method. The research tools consisted of 1) group discussion issues and 2) the caregivers’ participation model developed by the researcher. Data collection included an infection prevention behavior questionnaire and caregivers’ satisfaction towards nursing services questionnaire. The content validity indexes of the questionnaires were 0.91 and 0.93 respectively. Cronbach ‘s alpha coefficients of the questionnaires were 0.87, 0.93 respectively. Data were analyzed by using descriptive statistics, paired t-test, Wilcoxon matched pairs signed-ranks test, and Fisher’s Exact test. The research findings were as follows. Firstly, the caregivers’ participation model consisted of a guideline for caregivers’ participation in infection prevention from admission to discharge including teaching, demonstration, return demonstration, and essential skills training. Secondly, the caregivers reported that their overall and in each aspect of infection prevention behaviors after implementing the developed model was higher than before implementing the model significantly (p<.05). They also rated higher satisfaction towards the nursing services significantly after implementing the model (p<.05). Lastly, pediatric cancer patients’ readmission rates were statistically lower than before implementing the model (p<.05).